Tantangan dan Efektivitas Program KAREBA: Program Mengajar Mahasiswa Kampus Mengajar V di SD Makassar - Baharman, Baharman; Suriadi, Suriadi; Farid, Muh. (Nuances of Indonesian Language, 2024)
This study aims to determine the challenges and effectiveness of the Gerakan Lancar Membaca (KAREBA) program as a teaching program in reading assistance for students of SD Inpres Sambung Jawa 1 Makassar. KAREBA is a program designed by students of Teaching V campus to improve students' reading skills through a structured approach and active participation. The research method used was descriptive qualitative. The researcher made observations first, then interviewed 5 students of Teaching Campus V at SD Inpres Sambung Jawa 1 Makassar. The results showed that there were several challenges and effectiveness in implementing the KAREBA program at SD Inpres Sambung Jawa 1 Makassar. The challenges are student attendance and participation, motivation and interest in learning, and time management. Opportunities for these challenges include improved reading skills, parental and school support, and teaching methods. Based on this research, it can be concluded that the KAREBA program can be a reference for elementary school teachers in implementing this teaching program.